Risk of high‐grade cervical dysplasia and gynaecological malignancies following the cytologic diagnosis of atypical endocervical cells of undetermined significance: A retrospective study of a state‐wide screening population in Western Australia. (5th June 2015) - Munro, Aime; Williams, Vincent; Semmens, James; Leung, Yee; Stewart, Colin J.R.; Codde, Jim; Spilsbury, Katrina; Steel, Nerida; Cohen, Paul; O'leary, Peter
<x xml:space="preserve">Abstract</x> Background In 2006, Australia adopted a revised cervical cytology terminology system, known as the Australian Modified Bethesda System (AMBS). One substantial change in the AMBS was the introduction of the diagnostic category of atypical endocervical cells (AEC) of undetermined significance. Aim The aim of this study was to investigate the incidence of histologically confirmed high‐grade cervical dysplasia (cervical intra‐epithelial neoplasia (CIN) grades 2 and 3 and adenocarcinoma in situ (ACIS)), cervical carcinoma and endometrial carcinoma in women presenting with AEC on cervical cytology. Methods A seven‐year retrospective study examining clinical outcomes of women with AEC on a screening cervical smear. Cytology and histology results were extracted from the Western Australia Cervical Screening Registry, and time‐to‐event analysis was used to predict the odds of having or developing in situ and invasive neoplasia. Results AEC was reported in index smears from 0.093% (584/622754) women during the study period. No follow‐up was available in 35 AEC cases. Sixty‐five of the remaining 549 women (11.8%) had, or developed, high‐grade cervical dysplasia within five years of their index AEC diagnosis. Endometrial cancer was diagnosed in 21 women and cervical cancer in four women during the follow‐up period. Conclusion Cytologic demonstration of AEC requires careful gynaecologic evaluation, particularly in younger women who may be found to have either high‐grade squamous (CIN) or glandular (ACIS) lesions, while in older women, the possibility of endometrial neoplasia needs to be considered.